2008
DOI: 10.2337/dc07-1863
|View full text |Cite
|
Sign up to set email alerts
|

A1C in Children and Adolescents With Diabetes in Relation to Certain Clinical Parameters

Abstract: OBJECTIVE—We explored the relationship between A1C and insulin regimen, duration of diabetes, age, sex, and BMI as well as the differences between clinical mean A1C levels at pediatric diabetes clinics in Sweden. RESEARCH DESIGN AND METHODS—Data from 18,651 clinical outpatient visits (1,033 girls and 1,147 boys) at 20 pediatric clinics during 2001 and 2002 registered in the Swedish Childhood Diabetes Registry SWEDIABKIDS, a national quality registry, were analyzed. RESULTS—A1C was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
101
2
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(113 citation statements)
references
References 8 publications
9
101
2
1
Order By: Relevance
“…Children and adolescents with type 1 diabetes in Sweden are intensively treated with multiple insulin injections or insulin pump therapy and active self-control. Their glycaemic control is better than, or comparable to, other populations (13,24,25). Perhaps this intense treatment can help these patients to handle the stress of the colder Swedish climate, and more infections during the winter, and equalise the HbA1c values over the year.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Children and adolescents with type 1 diabetes in Sweden are intensively treated with multiple insulin injections or insulin pump therapy and active self-control. Their glycaemic control is better than, or comparable to, other populations (13,24,25). Perhaps this intense treatment can help these patients to handle the stress of the colder Swedish climate, and more infections during the winter, and equalise the HbA1c values over the year.…”
Section: Discussionmentioning
confidence: 99%
“…Girls aged between six and 12-years-of-age years of age were found to have higher HbA1c levels at diagnosis than boys of the same age and girls of other age groups (12). Moreover, poorer metabolic control has been found in girls than boys during the clinical course, especially during adolescence (13)(14)(15).…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Previous studies (2,3) have shown that improved glycaemic control, measured as HbA1c, is important in preventing, delaying or slowing the progression of long-term complications. A high proportion of adolescents do not reach treatment targets for glycated haemoglobin, HbA1c (4)(5)(6), and there is evidence that metabolic control deteriorates during adolescence. There is a correlation between metabolic control in late childhood and during adolescence (7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…However, optimal glycemic control is difficult to achieve in the 'real-world'. Observational population-based studies have indicated suboptimal levels of glycemic control worldwide despite the well-publicized results of the DCCT (Petitti et al, 2009;Johannesen et al, 2008;Hanberger et al, 2008;Gerstl et al, 2007).…”
Section: Introductionmentioning
confidence: 99%